1999
DOI: 10.1557/proc-594-37
|View full text |Cite
|
Sign up to set email alerts
|

Ion Implantation and Misfit Dislocation Formation in P/P+Silicon

Abstract: We determined that self implantation of pseudomorphically strained silicon epitaxial layers greatly attenuates strain relaxation. We employed highly boron doped 150 mm diameter silicon with a nominally un-doped, 2.5 μm thick epitaxial layer (p/p+). The compressively strained layer (mismatch ≈ 1.5 × 10−4) showed inhomogeneous relaxation after epitaxial growth, with misfits forming only near the wafer periphery. High temperature rapid thermal annealing was employed after ion implantation to study misfit dislocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 8 publications
2
4
1
Order By: Relevance
“…The in vivo ectopic bone formation data obtained above suggest that this GAM could play a role in approaches involving the latter. The data demonstrated that the highest frequency of bone formation (100%) was delivered with MAS and this is in line with previous studies showing that sonoporation can significantly increase the frequency of successful gene delivery and associated bone formation in vivo (Feichtinger et al, 2014a). The novel outcome of the current study regarding the significantly (5.4-to 16.4-fold) increased yields of bone volumes attainable with MAS ( Figure 4) compared to all other standard treatment modalities (passive GAM and sonoporation) is furthermore superior to those from previous studies by us and other groups in which multiple rounds of sonoporation and higher DNA doses were necessary for tissue formation (Feichtinger et al, 2014a;Osawa et al, 2009).…”
Section: Mas-mediated Gene Transfer and Osteogenesis In Vivosupporting
confidence: 91%
See 4 more Smart Citations
“…The in vivo ectopic bone formation data obtained above suggest that this GAM could play a role in approaches involving the latter. The data demonstrated that the highest frequency of bone formation (100%) was delivered with MAS and this is in line with previous studies showing that sonoporation can significantly increase the frequency of successful gene delivery and associated bone formation in vivo (Feichtinger et al, 2014a). The novel outcome of the current study regarding the significantly (5.4-to 16.4-fold) increased yields of bone volumes attainable with MAS ( Figure 4) compared to all other standard treatment modalities (passive GAM and sonoporation) is furthermore superior to those from previous studies by us and other groups in which multiple rounds of sonoporation and higher DNA doses were necessary for tissue formation (Feichtinger et al, 2014a;Osawa et al, 2009).…”
Section: Mas-mediated Gene Transfer and Osteogenesis In Vivosupporting
confidence: 91%
“…The data demonstrated that the highest frequency of bone formation (100%) was delivered with MAS and this is in line with previous studies showing that sonoporation can significantly increase the frequency of successful gene delivery and associated bone formation in vivo (Feichtinger et al, 2014a). The novel outcome of the current study regarding the significantly (5.4-to 16.4-fold) increased yields of bone volumes attainable with MAS ( Figure 4) compared to all other standard treatment modalities (passive GAM and sonoporation) is furthermore superior to those from previous studies by us and other groups in which multiple rounds of sonoporation and higher DNA doses were necessary for tissue formation (Feichtinger et al, 2014a;Osawa et al, 2009). In previous studies using a cell and matrix-free sonoporation-based approach it was necessary to use 100 μg of DNA and an ultrasound energy density of 90-600 J/cm 2 whereas here, 6.5 μg of DNA and an ultrasound energy density of 30 J/cm 2 were used (Feichtinger et al, 2014a).…”
Section: Mas-mediated Gene Transfer and Osteogenesis In Vivosupporting
confidence: 91%
See 3 more Smart Citations